Tasigna (nilotinib) in chronic myeloid leukemia treatment-free remission after nearly 2 years: an interview with Adam Mead. (November 2017) - Mead, Adam
Dr Mead earned his medical degree from the University of Oxford and trained in hematology at St Bartholomew's Hospital and University College London. In 2007, he earned his PhD at UCL, which focused on the analysis of FLT3 mutations in acute myeloid leukemia. He is now Associate Professor of Hematology and MRC Senior Clinical Fellow at the WIMM, University of Oxford. His research group focuses on myeloid diseases and normal blood stem-cell biology. Dr Mead is the lead clinician for myeloproliferative neoplasms (MPN) and chronic myeloid leukemia in the Thames Valley Strategic Clinical Network and is the chief investigator for several chronic myeloid leukemia and MPN clinical trials. Additionally, Dr Mead has helped shape the diagnostic and treatment guidelines for MPNs in the UK and serves as the chair of the MPN clinical study subgroup of the National Cancer Research Institute.